Advanced Technologies, Systems, and Applications - Hadžikadić, Mirsad; Avdaković, Samir (Lecture Notes in Networks and Systems, 2017)
This volume spans a wide range of technical disciplines and technologies, including complex systems, biomedical engineering, electrical engineering, energy, telecommunications, mechanical engineering, civil engineering, and computer science. The papers included in this volume were presented at the International Symposium on Innovative and Interdisciplinary Applications of Advanced Technologies (IAT), held in Neum, Bosnia and Herzegovina on June 26 and 27, 2016. This highly interdisciplinary volume is devoted to various aspects and types of systems. Systems thinking is crucial for successfully building and understanding man-made, natural, and social systems. .